"Recuperar el trabajo": Utopia and the Work of Recovery in an Argentine Cooperativist Movement - Faulk, Karen Ann (The journal of Latin American and Caribbean anthropology, 2016)
Resumen Desde su incepción como unidad ideológica, nacida del encuentro colonial, 'América Latina´ ha sido sujeto y productor de imaginarios idealizados del orden universal y el lugar de la humanidad dentro de él. Este artículo analiza las ideas y acciones de un movimiento cooperativista argentino, la Confederación Nacional de Cooperativas de Trabajo (CNCT), y las sitúa dentro de la historia más amplia de visiones utópicas latinoamericanas. Propongo que las ideas y reclamos avanzados por la CNCT tienen una estrecha relación con dos visiones utópicas fundamentals: las ideologías políticas marxistas y peronistas de la justicia social; y la idea de igualdad universal, especialmente como ésta se encuentra elaborada en el discurso normativo transnacional de los derechos humanos. La CNCT une estas visiones en diseñar un nuevo ideal utópico acorde con las realidades y necesidades del siglo veintiuno, absorbiendo, transformando y transcendiendo las visiones utópicas que la inspiran. [Argentina, autogestión, cooperativas, derechos humanos, economía social, trabajo] From its inception as an ideologically constituted unit born of the colonial encounter, Latin America has been a subject and producer of idealized imaginaries of a universal order and humanity's place within it. This article analyzes the ideas and actions of a recent Argentine cooperativist movement within a broader history of utopian visions within and across Latin American left‐wing movements. It looks specifically at the idea of work proposed by the Confederación Nacional de Cooperativas de Trabajo (CNCT). Founded in 2009, the CNCT pulls together some 30 federations of workers’ cooperatives from across Argentina. As an umbrella organization, it is designed to strengthen the ties among a diverse yet united array of experiences, and to advance a cooperativst project based on a defined set of economic and social principles, bringing together the recovery of work and worker self‐management as a stepping stone toward the creation of a new basis for economic life. Much of the literature on the recuperated businesses movement focuses on events surrounding the 2001 economic, social, and political crisis; this article, however, explores how the ideas promoted by the umbrella organizations draw on existing organizational, legal, and ideological structures that predate the structural changes of the 1990s. Drawing on recent scholarship on the anthropology of human rights and the anthropology of work, it argues that two strands of utopian visions operate in the formulation of the demands and ideals proposed by the CNCT. One is derived from both Peronist and Marxist political ideologies of social justice, especially as envisioned through the idealized figure of the worker. The other draws on the utopian ideal of universal equality as elaborated in the discursive field of human rights. The CNCT unites these visions in designing a new, 21st century utopian ideal of a Social Economy that inflects and transcends the utopian visions that inspire it. [Argentina, cooperatives, human rights, labor, self‐management, social economy, work]